2010
DOI: 10.1111/j.1365-2036.2010.04367.x
|View full text |Cite
|
Sign up to set email alerts
|

A model of healing of Los Angeles grades C and D reflux oesophagitis: is there an optimal time of acid suppression for maximal healing?

Abstract: Aliment Pharmacol Ther 2010; 32: 443–447SummaryBackground  In patients with Los Angeles (LA) grade C or D oesophagitis, a positive relationship has been established between the duration of intragastric acid suppression and healing.Aim  To determine whether there is an apparent optimal time of intragastric acid suppression for maximal healing of reflux oesophagitis.Methods  Post hoc analysis of data from a proof‐of‐concept, double‐blind, randomized study of 134 adult patients treated with esomeprazole (10 or 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 27 publications
0
10
0
1
Order By: Relevance
“…Therefore, we agree that treating patients on the basis of impedance – pH monitoring results rather than treating them empirically will result in increased treatment success 22 . However, impedance – pH monitoring should include oesophageal as well as gastric pH monitoring, as the efficacy of incremental PPI dosages for those patients (30% of cases in our series) with a GAET <30% would probably be low 17 . Recently, we have shown that laparoscopic fundoplication improves significantly symptoms as well as acid and weakly acidic reflux parameters when compared with high‐dose PPI therapy in refractory GERD patients 9 .…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Therefore, we agree that treating patients on the basis of impedance – pH monitoring results rather than treating them empirically will result in increased treatment success 22 . However, impedance – pH monitoring should include oesophageal as well as gastric pH monitoring, as the efficacy of incremental PPI dosages for those patients (30% of cases in our series) with a GAET <30% would probably be low 17 . Recently, we have shown that laparoscopic fundoplication improves significantly symptoms as well as acid and weakly acidic reflux parameters when compared with high‐dose PPI therapy in refractory GERD patients 9 .…”
Section: Discussionmentioning
confidence: 69%
“…Healing of reflux oesophagitis has been positively related to the percentage of time when intra‐oesophageal 15 and intra‐gastric pH 16 are >4. Recently, maximal reflux oesophagitis healing rates have been related to an intra‐gastric pH >4 for 70% or more of the 24‐h period: intra‐gastric pH control has then been proposed as a clinically relevant measurement of drug efficacy in the treatment of patients with moderate to severe reflux oesophagitis 17 . In our patients, one half of whom were treated with a standard PPI dosage, an intra‐gastric pH >4 was achieved for 70% of the time in only 30% of cases as a GAET >30% was detected in 70% of cases.…”
Section: Discussionmentioning
confidence: 99%
“…20 Moreover, Katz et al reported that reflux esophagitis, which is a type of GERD, was healed when the pH ࣙ 4 HTR was between 50% and 70% after repeated administration of esomeprazole for 4 weeks. 21 Therefore, our findings suggest that azeloprazole sodium is a promising drug for the treatment of GERD. Moreover, the mean pH ࣙ 4 HTR on the first day after administration of 40 mg azeloprazole sodium was similar to a 20-mg dose of rabeprazole.…”
Section: Discussionmentioning
confidence: 70%
“…It is known that pH 4 holding time over a 24-h period is directly related to GERD healing rate [23]; the period required to cure moderate-to-severe GERD is estimated at 70% [24]. In this study, pH 4 holding time values for 24-h periods at 40 mg of rabeprazole in homo-EMs, hetero-EMs, and PMs were 65.8%, 77.2%, and 83.1%, respectively (Table 3), and the corresponding values in hetero-EMs and PMs reached the suggested goal.…”
Section: Discussionmentioning
confidence: 99%